This preview shows pages 1–2. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: Math 118C Homework 3 Solutions Charles Martin April 21, 2009 9.19 Show that the system of equations 3 x + y z + u 2 = 0 x y + 2 z + u = 0 2 x + 2 y 3 z + 2 u = 0 can be solved in terms of x , in terms of y , in terms of z , but not in terms of u . For k = 1 , 2 , 3 define f k : R 4 → R by f 1 ( x, y, z, u ) = 3 x + y z + u 2 f 2 ( x, y, z, u ) = x y + 2 z + u f 3 ( x, y, z, u ) = 2 x + 2 y 3 z + 2 u. Let f : R 4 → R 3 be the map given by f = ( f 1 , f 2 , f 3 ). Clearly f is smooth and f (0 , , , 0) = 0. We can compute f (0 , , , 0); in the standard basis the Jacobian matrix is 3 1 1 1 1 2 1 2 2 3 2 Consider the problem of solving for y, z, u in terms of x in the equation f ( x, y, z, u ) = 0. By the implicit function theorem, this is possible since the determinant of the corresponding submatrix is nonzero: det 1 1 1 2 1 2 3 2 = 3 6 = 0 Similarly, the equation f ( x, y, z, u ) = 0 can be solved for x, z, u in terms of y since the corresponding submatrix has nonzero determinant: det 3 1 1 2 1 2 3 2 = 21 6 = 0 . Also, the same equation can be solved for x, y, u in terms of z because the corresponding submatrix is invertible: det 3 1 1 1 1 2 2 2 = 12 6 = 0 . Finally, suppose we try to solve f ( x, y, z, u ) = 0 for u . Treating u as a parameter, we can use techniques of linear algebra and attempt to solve the system via Gaussian elimination. 3 x + y z = u 2 x y + 2 z = u 2 x + 2 y 3 z = 2 u = ⇒ 3 1 1 u 2 1 1 2 u 2 2 3 2 u = ⇒ 1 1 2 u 4 7 u 2 + 3 u u 2 3 u We see that the equation is solvable only when...
View
Full
Document
This note was uploaded on 11/08/2011 for the course MATH 224 taught by Professor Gurel during the Spring '05 term at Boğaziçi University.
 Spring '05
 gurel
 Equations

Click to edit the document details